Curcumin Sustained Release with a Hybrid Chitosan-Silk Fibroin Nanofiber Containing Silver Nanoparticles as a Novel Highly Efficient Antibacterial Wound Dressing - Parisa Heydari Foroushani; Erfan Rahmani; Iran Alemzadeh; Manouchehr Vossoughi; Mehrab Pourmadadi; Abbas Rahdar; Ana M. Díez-Pascual (Nanomaterials, 2022)
Drug loading in electrospun nanofibers has gained a lot of attention as a novel method for direct drug release in an injury site to accelerate wound healing. The present study deals with the fabrication of silk fibroin (SF)-chitosan (CS)-silver (Ag)-curcumin (CUR) nanofibers using the electrospinning method, which facilitates the pH-responsive release of CUR, accelerates wound healing, and improves mechanical properties. Response surface methodology (RSM) was used to investigate the effect of the solution parameters on the nanofiber diameter and morphology. The nanofibers were characterized via Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), zeta potential, and Dynamic Light Scattering (DLS). CS concentration plays a crucial role in the physical and mechanical properties of the nanofibers. Drug loading and entrapment efficiencies improved from 13 to 44% and 43 to 82%, respectively, after the incorporation of Ag nanoparticles. The application of CS hydrogel enabled a pH-responsive release of CUR under acid conditions. The Minimum Inhibitory Concentration (MIC) assay on E. coli and S. aureus bacteria showed that nanofibers with lower CS concentration cause stronger inhibitory effects on bacterial growth. The nanofibers do not have any toxic effect on cell culture, as revealed by in vitro wound healing test on NIH 3T3 fibroblasts.